2013
DOI: 10.1007/s40519-013-0078-z
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of selected iron management parameters and activity in food-restricted female Wistar rats (animal anorexia models)

Abstract: AimsThe aim of this study was to assess the influence of food-restricted diets (anorexia models) on iron management and activity of rats.Materials and methods48 rats were divided into 6 groups: 1 control (K) and 5 testing groups (K/2, GI, GII, GIII, GIV). K was fed ad libitum. K/2 received half the portion of the diet of K. The other groups received 100 % of the diet eaten by K, but with different models of food restriction: GI—1 day on, 1 day starvation; GII—2 days on, 2 days starvation; GIII—3 days on, 3 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The elevated hematocrit observed in adolescent ABA rats of both sexes, and adolescent male FC rats, is at odds with reports of reduced hematocrit levels in food restricted rats (Wojciak, 2014) and patients with severe AN [but see Symreng et al (1985), Sabel et al (2013)]. Instead, increased hematocrit is usually observed after excessive exercise in humans (Skarpańska-Stejnborn et al, 2015) but not rodents (Tian et al, 2012; Tang et al, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…The elevated hematocrit observed in adolescent ABA rats of both sexes, and adolescent male FC rats, is at odds with reports of reduced hematocrit levels in food restricted rats (Wojciak, 2014) and patients with severe AN [but see Symreng et al (1985), Sabel et al (2013)]. Instead, increased hematocrit is usually observed after excessive exercise in humans (Skarpańska-Stejnborn et al, 2015) but not rodents (Tian et al, 2012; Tang et al, 2019).…”
Section: Discussionmentioning
confidence: 91%
“…Wojciak et al examined the effect of five different feeding regimens on iron and hemoglobin levels in the blood of rats (Wojciak, 2014 ). They had one group that received 50% of the food intake of a control group.…”
Section: Resultsmentioning
confidence: 99%
“…The fourth group had 3 days ad libitum access alternating with 3 days of no access to food. The fifth group had 4 days ad libitum access to food and 4 days no access to food (Wojciak, 2014 ). They found that the longer the starvation the stronger the negative effect on blood concentrations of hemoglobin, hematocrit, RBC, serum ferritin and iron levels in different organs (but even in rats with acute starvation a decrease in these parameters was observable) (Wojciak, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…During treatment with 20 mg/kg of As, dams showed decreases in body weight gain and food consumption. Maternal undernutrition may induce prenatal stress (Cox et al, 2011;Wojciak, 2014), which can result in impaired neurodevelopment. Indeed, rat models of maternal undernutrition have resulted in adult offspring with alterations in learning and memory, increased anxiety, and alterations in monoamine contents (Pallares et al, 2007;van den Hove et al, 2010;Zuena et al, 2008).…”
Section: Discussionmentioning
confidence: 99%